A magyar sajtófőnök "tudtával és segítségével”: Háborús portrévázlat kérdőjelekkel – Ullein-Reviczky Antal (1942-1944) = "With the knowledge and help" of the Hungarian press chief: a wartime portrait with question marks - Antal Ullein-Reviczky (1942-1944) - Joó, András (Közép-Európai Közlemények, 2017)
Antal Ullein-Reviczky, highly intellectual, witty and assertive, remains one of the most interesting and dynamic fi gures in the history of Hungary’s eff orts to leave the German orbit during the fateful years of the Second World War. He seems to be, at the same time, one of the controversial characters among Hungarian diplomats who were involved in secret negotiations, at least as far as the judgement of some of his contemporaries suggests. For more than a year he was not only Head of the Foreign Ministry Press Department, but also held the position of Press Chief in the Premier’s Offi ce. He had a key impact upon the Hungarian Press under two Prime Ministers, László Bárdossy and Miklós Kállay. The latter was said to have relied mainly on Ullein-Reviczky, who had confl icts and a tense relationship with the Political Department of the Foreign Ministry. Kállay gradually turned towards the offi cials of the Political Department. Later, from the autumn of 1943, Ullein-Reviczky, as Hungarian Minister, had a key role in secret talks with the Allies in Stockholm. There were numerous eff orts to engage in secret negotiations with allied representatives, and early 1944 he encouraged his superiors in Budapest to take the initiative and direct peace-feelers towards the Soviet Union as well. Although a frequent target of criticism, Ullein-Reviczky had great merits, took some brave initiative, and in journalists he left behind good memories, having been a tactful and benevolent ‘censor’ who applied persuasion instead of oppression.